(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Liver resection was performed on 60 white mongrel rats where 70% of the liver was resected. Pieces were taken for anatomical and histological studies. For anatomical and histological studies For the studies, pieces were taken on days 3, 7 and 14. For the study of microvessels, the following were used: filling with Gerot mass and 2% gelatin-tussula through the aorta. Sections of 5-30 μm thickness were prepared. After liver resection, the size of pancreatic microvessels increased by more than 50%. Intralobular hemorrhages and microthrombi in the vessels were observed. Foci of hemorrhage were observed in the islets of Langerhans., the microvessels of the pancreas were mainly manifested in the form of dystrophic, atrophic and inflammatory changes in the endocrine part and necrosis of excretory cells.